Hybrid Framework Parameterization Reduction Combination in Soft Set - Mohammed, Mohammed Adam Taheir; Wan Maseri, Wan Mohd; Ruzaini, Abdullah Arshah; Mungad, M.; Sutoyo, Edi; Chiroma, Haruna (2015)
Voluminous data are available in soft sets,which makes itdifficult to recognize the soft set decisions of the data.The large increase in the volume of these soft set has made it necessary to enlarge the size of the storage media to store the data. Consequently,several researches have proposeds oft set reduction of the data. This paper proposes uncertain soft set by hybridizing two soft set reduction techniques producing a significant result without affecting the decisive characteristics of the data. This proposed method utilizes advanced techniques to govern knowledge with proper reduction of related resources that can assist the decision making process.